An investigation into minichromosomal maintenance proteins (MCMs) for the diagnosis of prostate cancer, as a possible alternative to prostate specific antigen (PSA) - Watkins, Jane Louise (Cranfield University, 2005)
The current strategy for the diagnosis of prostate cancer includes serum prostate specific antigen (PSA) measurement. There is however debate into its specificity and sensitivity, so new diagnostic markers are under investigation. Minichromosomal maintenance proteins (MCMs) are potential markers for the diagnosis of neoplasia, as they are involved in cellular replication. The aim of this study is to assess MCM2, 5 and 7 as new diagnostic markers for prostate cancer, to compare the clinical usefulness of PSA and to develop a less invasive technique for diagnosis. PSA specificity was investigated in several human cellular lines, and a clinical study was performed to assess expression in prostatic tissue and blood serum. MCM2, 5 and 7 was investigated by translational and transcriptional means in two prostate cell lines PNT1A and PC-3. In addition, a clinical study was performed to assess the expression of MCM2, 5 and 7 in prostate tissue, urine and blood The results suggest that PSA is not prostate specific, as it is synthesised and secreted by several non-prostatic cell lines. In addition PSA testing does not conclusively indicate neoplastic tissue and serum testing only has 63% sensitivity and 60% specificity in accurately identifying prostate cancer. The in vitro results suggest that the PC-3 cells express less MCM2, 5 and 7 on both the protein and mRNA level compared to the PNT1A cells, suggesting that MCM2, 5 and 7 maybe performing a bigger role than just replication of DNA. The tissue results indicate that there is an increase in MCM2, 5 and 7 epithelial nuclei staining for neoplastic condition compared to BPH. While the clinical study on urine sediment indicates increased MCM2, 5 and 7 staining in prostatic neoplasia compared to BPH and the transcriptional study on MCM5 can identify neoplastic tissue from BPH as 11/12 cancerous patients expressed MCM5 compared to only 3/23 BPH patients. Finally the transcriptional study on the blood samples is inconclusive and need to be repeated These results suggest that serum PSA testing is not ideal for the diagnosis of prostate cancer, that MCM2, 5 and 7 appear to have potential as new diagnostic markers and may aid the histopathologist to allocate Gleason score. Also the MCMs may have potential in the development of a less invasive technique through the use of urine sediment.